Electrical charge transport and optical properties of a poly(methacrylate) with a new side chain and its Ni(II) complex - Yakuphanoğlu, Fahrettin; Sarman, S; Aydogdu, Y; Ilter, Z; Coskun, M (John Wiley & Sons Inc, 2003)
The electronic conductivity of poly[2-(2-hydroxybenzyliden hydrazino)thiazole-4-yl methyl methacrylate] bearing a thiazole ring, Schiff base, and hydroxyl group in its side chain and its Ni(II) complex were measured as functions of temperature and frequency. The electrical measurements show the semiconducting nature of the samples as their electrical conductivity increased with increased temperature. Also, the activation energies were below 2 eV, which places them in the semiconductor regime. The conduction mechanism in the samples is discussed. Although extrinsic conduction mechanism occurs in the polymer, intrinsic conduction mechanism take places in its metal complex. The optical absorption spectra were recorded at room temperature and the optical energy gaps of samples were determined by optical spectra. (C) 2002 Wiley Periodicals, Inc.
Keywords: polymer; metal complex; conductivity; activation energy